Kemampuan Mengidentifikasi Penulisan GOI yang mengandung Chouon pada Siswa SMA N 1 KINALI - Edo Setiawan; Nova Yulia (Universitas Negeri Padang, 2022)
This research was motivated by the difficulties of students in identifying chouon (long vowels) found in goi (vocabulary). This study aims to determine the ability to write goi containing chouon in class X SMA N 1 Kinali in the academic year 2020/2021 in more detail according to the curriculum applied at school. This research was conducted at SMA N 1 Kinali in July 2021. This type of research is quantitative and the research method is descriptive. The population in this study were students of class X SMA N 1 Kinali in the academic year 2020/2021. The sample in this study were students of class X BB SMA N 1 Kinali totaling 32 students. The sampling technique used in this study is a purposive sample technique. The data in this study is the score of the goi writing ability test which contains chouon. Based on the results of the study, it is known that the ability to write goi containing chouon ii, uu, ei and ou has various values. The highest student chouon ability is at chouon uu with an average of 64 and the lowest is at chouon ei with an average value of 49, overall students' abilities have an average of 56 still in poor qualifications.